ANALISIS PENGELOLAAN DANA BOS DALAM MENGINGKATKAN MUTU PENDIDIKAN PADA SEKOLAH MENENGAH PERTAMA DI KABUPATEN ROKAN HILIR (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractProgram School Operational Assistance (BOS) is one form of education that significant funding sourced from the State Budget. The program is intended to reduce the burden on the poor in education funding, equity and expanding access and to improve the quality of education within the framework of compulsory education of nine years and continued for up to twelve years. This research is a qualitative descriptive study using a case study approach. Data were collected through interviews, observation and document study. Respondents in this study consisted of principals, teachers, school committees and parents. This study aims to analyze and describe how the effectiveness, accountability and transparency in the management of school operational funds to the junior high school in Rokan Hilir. The results are expected BOS management has been effective in improving access and quality of education at secondary school. Giving adequate priority to poor students is reached. Use of the funds absorbed not only for the payment of honorariums to teachers and employees. Accountability and transparency in the management of BOS funds should not be weak, it causes the use of the funds is not known teachers and school committees as a means of control in planning and in the use of funds. The mechanisms that ensure the management to be transparent, so that the BOS program management accountability is maintained.Keywords: Effectiveness, Accountability and Transparency